Romanticism in the history of Croatian literature - Meić, Perina (Poznańskie Studia Slawistyczne, 2011)
The paper researches the way romanticism is reconstructed and interpretated in three books on the history of Croatian literature (Ježić, Frangeš Jelčić). In the analysis of selected histories of Croatian literature, three very important methodological questions that are extracted, namely the question of periodization, the question of the evaluation of Croatian literature of romanticism, and the question of considering the Croatian literature of romanticism in the broader context of the literary world trends.